Effective Factors on Correct Diagnosis and Timely Interventions for Autism Spectrum Disorders in Children - Leili Mohamadi ghanatghestani; Mansureh Shahriari Ahmadi; Parisa Tajali (Iranian Journal of Educational Research, 2024)
Objective: Prevention and control of the disease in children with autism spectrum disorders in a country requires policies and decisions as well as accurate statistics and information in this field. Therefore, the present study was conducted with the aim of investigating the effective factors for correct diagnosis and timely interventions in autism spectrum disorders in children under 7 years of age. Methods: In this cross-sectional study, information on 83 children with autism spectrum disorder under 7 years of age diagnosed in Tehran using the Gilliam 3 Autism Measurement Scale, Connors Measurement Scale, PEP3 diagnostic test, and the researcher-made diagnostic package was examined. The collected data were analyzed using descriptive statistics, including mean and frequency, and inferential statistics, including chi-square and analysis of variance. Results: After analyzing the data using SPSS software, it was found that the three components of tool, age and severity of disorder are the most important factors contributing to correct diagnosis and timely intervention in autism spectrum disorders in children under 7 years of age. Conclusions: Considering that the results of this study have shown that the three components of tool , age and severity of the disorder are effective for timely diagnosis, it is suggested that families use testing as soon as they see the slightest symptoms in their children at a young age. It is appropriate to diagnose this disorder early, which can lead to partial control of this disease in children.